Color in packaging / Shahrul Azmeer Azman - Azman, Shahrul Azmeer (Faculty of Art and Design, 2020)
Consumers in the purchase of goods, first impressions are colour, and then shape, in the initial contact with the goods within 20 seconds, 80% colour sense, 20% sense form, related studies have shown that colour has pioneered momentum (Singh & Srivastava,2011). In the design of goods packaging, graphics and text depend on colour coordination, in other words, colour is the key to packaging design. As a commercial packaging design, colour has more visual impact on the promotion of goods, consumer desire to buy will have a direct effect. The same colour will cause people in different regions to associate different habits, produce different feelings or even conflict with love and hate, so the success of the packaging design, in large part, also depends on the local custom and aesthetic colours. Today, the colour design of the packaging has become public to evaluate the quality of the goods as intuitive indicators. Colour as a design element in packaging design cannot be ignored. On the other hand, visual advertising doesn't always sell a product directly, sometimes it sells an idea, a vision or even a fantasy relating to what a brand has to offer. Designers and advertising creatives rely on several tactics to optimize the reach and success of their visual advertising. Some of these approaches seem mostly technical, but there's still a lot of psychology involved.